Key Success Factors for Co-Working Space Business Model - Kuras Purba; Yusuf Ronny Edward (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
Co-working spaces have gained popularity in recent years as a flexible and cost-effective solution for freelancers, startups, and small businesses looking for a collaborative work environment. This article examines the key success factors for a co-working space business model, drawing on insights from industry experts and research studies. By identifying these critical factors, co-working space operators can optimize their business model and enhance their chances of success in a competitive market. The development of the use of co-working space is now increasingly promising. Many of the startup companies and freelancers who use co-working space as a place for daily activities to work. Co-working space also helps to differentiate work and daily activities from these workers. However, the business model of co-working space is relatively vulnerable. This study aims to evaluate the factors that can increase the success of the co-working space business model, considering the importance of co-working space as the development of creativity. This study involved 116 users from two businesses that achieved success in managing the co-working space. Data was collected using a questionnaire survey and structurally analyzed using SmartPLS. The results of the study identified that shared workspace management and supporting co-working space operations played an important role in determining the success of this business model. Membership management has no significant effect. Therefore, the management of co-working space can be focused on these two elements